Regulation of PXR function by coactivator and corepressor proteins: ligand binding is just the beginning - Rigalli, Juan Pablo; Theile, Dirk; Nilles, Julie; Weiß, Johanna (Cells, 2021)
The pregnane X receptor (PXR, NR1I2) is a nuclear receptor which exerts its regulatory function by heterodimerization with the retinoid-X-receptor α (RXRα, NR2B1) and binding to the promoter and enhancer regions of diverse target genes. PXR is involved in the regulation of drug metabolism and excretion, metabolic and immunological functions and cancer pathogenesis. PXR activity is strongly regulated by the association with coactivator and corepressor proteins. Coactivator proteins exhibit histone acetyltransferase or histone methyltransferase activity or associate with proteins having one of these activities, thus promoting chromatin decondensation and activation of the gene expression. On the contrary, corepressor proteins promote histone deacetylation and therefore favor chromatin condensation and repression of the gene expression. Several studies pointed to clear cell- and ligand-specific differences in the activation of PXR. In this article, we will review the critical role of coactivator and corepressor proteins as molecular determinants of the specificity of PXR-mediated effects. As already known for other nuclear receptors, understanding the complex mechanism of PXR activation in each cell type and under particular physiological and pathophysiological conditions may lead to the development of selective modulators with therapeutic potential.